Is Our Newborn Screening Working Well? A Literature Review of Quality Requirements for Newborn Blood Spot Screening (NBS) Infrastructure and Procedures - Birgit Odenwald; Inken Brockow; Marianne Hanauer; Anja Lüders; Uta Nennstiel (MDPI AG, 2023)
Newborn screening using dried blood spots (NBS) is widely acknowledged as a highly successful procedure in secondary prevention. For a number of congenital disorders, severe disability or death are impressively prevented by early detection and early treatment through NBS. However, as with any other screening, NBS can also cause harm, and the principle that "the overall benefits of screening should outweigh the harms" must be considered when introducing and implementing NBS programmes. This publication compiles the results of a systematic literature research on requirements for NBS infrastructure and procedures which was conducted as part of a research project on the quality and shortcomings of the NBS pathway in Germany. The compilation contains the requirements and recommendations for realising the principle of "maximise benefits and minimise harms" in relevant NBS pathway components such as parental education and information, coverage, timeliness, laboratory quality assurance, follow-up of abnormal results, confirmatory diagnostics, documentation, and evaluation. The results reflect the complexity of NBS infrastructure, and thus, they illustrate the importance of considering and implementing NBS as a well-coordinated public health programme with continuous quality management. Special attention should be paid to the perspectives of parents and families. Some NBS issues can substantially benefit from digital instruments or international cooperation. The literature review presented here has contributed to a concept of proposals for the advancement of NBS in Germany, and despite different settings, it may as well be of interest for other countries to achieve the best possible course and outcome of NBS for each child.